(untitled) (Tempo e Argumento, 2009)
The article examines some issurs about the History of the Present Time approach establishing relationships with Dictatorships of National Security. The reflections about the Present Time as a field of analysis of History express: the attempt to delimit this fields of analysis and of intervention from the historians; the adequacy of her theorical-methodological apparatus and the elaboration of new instruments which may enable him to face properly the challenge of the historical acceleration in the last decades.